Fabrication and Magnetic Properties of Mn1 - xZnxFe2O4 (0 ≤ x ≤ 0.8) Nanoparticles - Linh, Pham Hoai; Thanh, Tran Dang; Manh, Do Hung; Thuan, Nguyen Chi; Hong, Le Van; Phuc, Nguyen Xuan (Communications in Physics, 2009)
In this paper, we report results on the fabrication and magnetic properties of spinel ferrite Mn1-xZnxFe2O4 (0 ≤ x ≤ 0.8) nanoparticles. The nanoparticles were synthesized by a co-precipitation method. The effects of substituting Zn for Mn on the magnetic properties and particles size were focused. It was found that the phase-formation temperature is 90OC and the average particle size decreases from 40 nm to 10 nm when increased Zn concentration from zero to 0.8. The Curie temperature TC strongly decreases from 585 K (x = 0) to 320 K (x = 0.8) concomitantly with a decrease of the saturation magnetization MS. With a TC of 320 K and MS of 17 emu/g, the x=0.8 sample could be a promising candidate for some biomedical applications